REMOVAL AND FATE OF TOTAL AND FREE CYANIDE TREATING REAL LOW LOADED PETROCHEMICAL WASTEWATER IN A PILOT MEMBRANE BIOREACTOR (MBR) - F. Fatone; S. Di Fabio; F. Aulenta; M. Majone; A. Tapparo; F. Cecchi; G. Vecchiato; M. Busetto (Chemical Engineering Transactions, 2009)
Not available.